Efeitos dos sucos de frutas do cerrado maranhense na viabilidade de cepas probióticas e em modelos de endotoxemia experimental - ZAGMIGNAN, Adrielle (2020)
Endotoxemia is a life-threatening clinical condition, characterized by an impaired systemic response that causes multiple organ dysfunction and represents a serious problem for care with the health system worldwide. Some evidence has shown strong immunomodulatory effects induced by probiotic bacteria in experimental models of inflammatory disorders. It is associated with the use of fruits as a vehicle for the growth of these probiotic bacteria. In this context, the intake of fermented juice of Lacticaseibacillus rhamnosus (L. rhamnosus) in mice submitted to lipopolysaccharide-induced endotoxemia (LPS). After optimizing the best cultivation condition for L. rhamnosus in different pulp concentrations in cupuaçu juice, in addition to better production of lactic acid, the C57BL / 6 mice (n = 12 / group) were randomly allocated to experimental groups that received doses oral (100 µL / mouse) of phosphate buffered saline (PBS), unfermented cupuaçu juice or cupuaçu juice fermented by L. rhamnosus (resulting 108CFU / mL) for five days. Each animal was placed in an individual cage and received an intraperitoneal injection of LPS and was sacrificed after 6 h and 120 h after inoculation with LPS. The severity of endotoxemia was also daily evaluated. Every day, body weight and temperature were recorded and compared with data obtained before inoculation of LPS (baseline). The organs of each animal were weighed and measured, in addition to the puncture of cardiac blood to measure total and differential cells. The main results obtained suggest that the administration of L. rhamnosus-fermented juice reduced the severity of LPS-mediated endotoxemia, reduced weight loss, amended the migration of cells to peritoneal cavity and reduced the increase of cells in blood. In conclusion, our data show that early therapy of fermented cupuaçu juice with Lacticaseibacillus rhamnosus ATCC 9595 can reduce systemic inflammation in an experimental model of sepsis in mice.